MARKET SENTIMENT WITH ARTIFICIAL INTELLIGENCE: A REVOLUTION IN THE DIGITAL ECONOMY - Lucky Mahesa Yahya; Silvia Ekasari; Haryanto (CV. Adiba Aisha Amira, 2025)
The digital age has brought about a massive transformation in many sectors, including market sentiment analysis. The existence of big data from the internet, especially social media and online reviews, requires advanced technology to process and analyze it. Artificial Intelligence (AI) with Natural Language Processing (NLP) and machine learning capabilities are key in this revolution, especially in identifying and interpreting public sentiment towards products, services, or brands. The research method used is literature by looking for references that are in accordance with the research context. The research findings show that the integration of AI in market sentiment analysis has significant potential in improving the understanding of consumer sentiment. AI not only accelerates the process of analyzing vast data, but also increases the accuracy in interpreting sentiments and emotions. In particular, the use of machine learning models has enabled the adaptation and continuous improvement of sentiment analysis performance, providing deeper and more predictive insights into market trends.